Systematic genetic analysis of early-onset gout: ABCG2 is the only associated locus. (30th January 2020) - Zaidi, Faseeh; Narang, Ravi K; Phipps-Green, Amanda; Gamble, Greg G; Tausche, Anne-Katherin; So, Alexander; Riches, Philip; Andres, Mariano; Perez-Ruiz, Fernando; Doherty, Michael; Janssen, Matthijs; Joosten, Leo A B; et al.
Abstract: Objective: The aim of this study was to examine whether serum urate-associated genetic variants are associated with early-onset gout. Methods: Participants with gout in the Genetics of Gout in Aotearoa study with available genotyping were included ( n = 1648). Early-onset gout was defined as the first presentation of gout <40 years of age. Single nucleotide polymorphisms (SNPs) for the 10 loci most strongly associated with serum urate were genotyped. Allelic association of the SNPs with early-onset gout was tested using logistic regression in an unadjusted model and in a model adjusted for sex, body mass index, tophus presence, flare frequency, serum creatinine and highest serum urate. The analysis was also done in two replication cohorts: Eurogout ( n = 704) and Ardea ( n = 755), and data were meta-analysed. Results: In the Genetics of Gout in Aotearoa study, there were 638 (42.4%) participants with early-onset gout. The ABCG2 rs2231142 gout risk T-allele was present more frequently in participants with early-onset gout compared with the later-onset group. For the other SNPs tested, no differences in risk allele number were observed. In the allelic association analysis, the ABCG2 rs2231142 T-allele was associated with early-onset gout in unadjusted and adjusted models. Analysis of the replication cohorts confirmed the association of early-onset gout with the ABCG2 rs2231142 T-allele, but not with other serum urate-associated SNPs. In the meta-analysis, the odds ratio (95% CI) for early-onset gout for the ABCG2 rs2231142 T-allele was 1.60 (1.41, 1.83). Conclusion: In contrast to other serum urate-raising variants, the ABCG2 rs2231142 T-allele is strongly associated with early-onset gout.